Derecho cultural y amparo del coleo en el marco de la protección animal en el ordenamiento jurídico colombiano (Tema Central) - Duarte Molina, Tirson Mauricio (2020)
The recognition of cultural manifestations in the Colombian jurisdiction becomes malleable when it comes to identifying, protecting and guaranteeing the rights related. The doctrine has identified the principles and inner characteristics of these manifestations, without finding a unified position regarding the way of building the culture from the individual or their participation in the surrounded collective. The above has generated a Colombian system where it is not considered itself a unified criterion on the notion of culture and the cultural right by which it is protected, as well as the prerogatives that must be given before its concession. Thus, before the guiding questions, what is culture? And what should be considered as a cultural manifestation? It has become necessary to establish a boundary of these categories in order to understand objectively when a practice should or should not be covered by cultural law; and for this, it’s used the culturality test as a method for determining practices as cultural manifestations. For a concrete case, the practice known as “coleo” appears, where there is a divergence between cultural law and animal protection, a characterization and analysis is carried out in the light of this protection of wildlife and the principles that underlie cultural protection as a validation of their cultural essence.